Adult-onset leukoencephalopathy with axonal spheroids and pigmented glia: Clinical and imaging characteristics. Issue 2 (April 2019) - Makary, Mina S; Awan, Usama; Kisanuki, Yaz Y; Slone, Hasel W
Adult-onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) is a rare white matter degenerative disease characterized by both axonal and glial injury due to a defect in the CSF1R gene. In this report, we describe ALSP in a previously healthy 40-year-old woman presenting with insidiously progressive confusion, memory loss, and loss of social inhibitions. Characteristic magnetic resonance imaging findings for ALSP elucidated the diagnosis, including chronic foci of diffusion restriction in a non-vascular distribution, lack of temporal/infratentorial involvement, cortical sparing, and lack of enhancement. CSF1R genetic testing further confirmed the diagnosis and the patient underwent supportive medical management for symptom control. ALSP can pose a unique diagnostic challenge given its particular adult-onset presentation, but early recognition is key given the poor prognosis and the potential for family genetic testing.